MAHLI at the Rocknest sand shadow: Science and science‐enabling activities. Issue 11 (20th November 2013) - Minitti, M. E.; Kah, L. C.; Yingst, R. A.; Edgett, K. S.; Anderson, R. C.; Beegle, L. W.; Carsten, J. L.; Deen, R. G.; Goetz, W.; Hardgrove, C.; Harker, D. E.; Herkenhoff, K. E.; et al.
Abstract [1] During Martian solar days 57–100, the Mars Science Laboratory Curiosity rover acquired and processed a solid (sediment) sample and analyzed its mineralogy and geochemistry with the Chemistry and Mineralogy and Sample Analysis at Mars instruments. An aeolian deposit—herein referred to as the Rocknest sand shadow—was inferred to represent a global average soil composition and selected for study to facilitate integration of analytical results with observations from earlier missions. During first‐time activities, the Mars Hand Lens Imager (MAHLI) was used to support both science and engineering activities related to sample assessment, collection, and delivery. Here we report on MAHLI activities that directly supported sample analysis and provide MAHLI observations regarding the grain‐scale characteristics of the Rocknest sand shadow. MAHLI imaging confirms that the Rocknest sand shadow is one of a family of bimodal aeolian accumulations on Mars—similar to the coarse‐grained ripples interrogated by the Mars Exploration Rovers Spirit and Opportunity—in which a surface veneer of coarse‐grained sediment stabilizes predominantly fine‐grained sediment of the deposit interior. The similarity in grain size distribution of these geographically disparate deposits support the widespread occurrence of bimodal aeolian transport on Mars. We suggest that preservation of bimodal aeolian deposits may be characteristic of regions of active deflation, where winnowing of the fine‐sediment fraction results in a relatively low sediment load and a preferential increase in the coarse‐grained fraction of the sediment load. The compositional similarity of Martian aeolian deposits supports the potential for global redistribution of fine‐grained components, combined with potential local contributions.